Percutaneous Lapidus Procedure for the Management of Primary Hallux Valgus Deformity – A Retrospective Cohort Analysis - Alasdair John Henry Barrie MBChB MSc FRCS; James Ryeburn BSc; Alastair S.E. Younger MB ChB, ChM, FRCSC; Andrea Veljkovic MD, MPH, BComm, FRCSC; Kevin Wing MD, FRCSC; Murray J. Penner MD, FRCSC; Oliver Gagne MD, FRCSC (Foot & Ankle Orthopaedics)
Category: Bunion; Midfoot/Forefoot Introduction/Purpose: Hallux valgus deformity remains prevalent in elective foot and ankle practice, affecting approximately 35% of adults aged over 65. When conservative treatments fail, surgical interventions like osteotomies or fusions are considered. The Lapidus procedure offers significant correction but traditionally involves open incisions. Percutaneous techniques have emerged to minimize soft tissue trauma, reduce postoperative pain, and expedite recovery. Our technique entails percutaneous preparation of the first tarsometatarsal joint using a Shannon burr for debridement, arthroscopy for visualization, and fixation with three full thread 4 mm non-variable pitch headless chamfered cannulated screws, preserving subchondral bone for stability. We aim to assess postoperative complications and radiographic correction achieved following primary hallux valgus surgeries using our percutaneous Lapidus procedure as the default surgical technique of the lead author. Methods: Patients aged 16 and above who underwent the percutaneous Lapidus procedure for primary hallux valgus deformity between January 1st, 2018, and April 1st, 2023, were retrospectively identified in our database. Inclusion criteria required a minimum of 6-month postoperative follow-up. Individual patient records and radiographic imaging were then reviewed retrospectively. 149 percutaneous Lapidus procedures were performed for primary hallux valgus in 130 patients. 19 patients underwent bilateral surgeries. 12 patients were male (9.2%). The mean follow-up period was 34 months (range: 6–70 months). 47 cases (31.5%) had percutaneous akin osteotomy in addition to percutaneous Lapidus. Outcome measures included revision surgeries and pre- and post-operative Intermetatarsal angle (IMA): normal < 9º, Hallux valgus angle (HVA): normal less than 15º, Distal articular metatarsal angle (DMMA): normal less than 10º and Sesamoid station measured as the distance between the lateral cortex of the first metatarsal and lateral cortex of the lateral sesamoid. Results: No cases of deep infection or non-union requiring revision surgery were identified during follow-up. Metalwork was removed for irritation in 17 cases (11.4%) at mean 17 months (range: 6–33 months) from surgery. Subsequent ipsilateral first metatarsophalangeal joint fusion for symptomatic arthritis occurred in 3 patients (2%) at mean 24 months (range: 8–40 months) from surgery. Complete pre and post-surgical radiographic imaging was available in 134 cases (90%). IMA reduced from mean 15.8 degrees (95% CI: 15.2-16.5) to mean 6.4 degrees (95%CI: 5.9-6.9). HVA reduced from mean 32.3 degrees (95%CI: 30.7-33.9) to mean 12.2 degrees (95%CI: 11.1-13.2). DMMA reduced from mean 30.6 degrees (95%CI: 28.6-32.7) to mean 10.1 degrees (95%CI: 9-11.2). Sesamoid station reduced from mean 9mm (95%CI: 8.5-9.5) to mean 2.8mm (95% CI: 2.4-3.2). Conclusion: In our experience percutaneous Lapidus fusion of the first tarsometatarsal joint appears to be a safe and effective treatment for primary hallux valgus. Within our cohort, we observed no instances of nonunion of the first tarsometatarsal joint with a minimum of 6-month follow-up. Incidents of postoperative soft tissue irritation requiring the removal of metalwork appear comparable to those reported in open techniques for primary hallux valgus treatment. We feel that in our cohort satisfactory radiographic correction was achieved in a wide spectrum of deformities.